(untitled) (Revista de Biología Marina y Oceanografía, 2024)
Biofouling is generated by the biochemical condition of the substrate to form complex communities; this could be negative at an ecological and industrial level. To inhibit this process, coatings based on heavy metals are used. Microorganisms are promising sources of antifouling compounds that are non-toxic or less toxic than the commercial chemicals in use today. In order to evaluate the antifouling effectiveness of bacterial extracts, seven crude extracts from cultures of bacteria isolated from marine organisms were obtained. They were subjected to a toxicity test with Artemia nauplii, at different concentrations. Non-toxic extracts were incorporated into a gelling agent (Phytagel™) and exposed to the sea for 30 days to evaluate the inhibition of diatoms and macroorganisms adhesion. Sixty-seven diatoms’ taxa were identified, belonging to 45 genera, besides four groups of non-photosynthetic macroorganisms were identified; these are sea squirts, barnacles, bryozoans, and polychaetes. Toxicity test showed that only Bacillus safensis (C2) extract was toxic, and it was excluded from subsequent tests. There are significant differences between treatments, the extracts with the best activity are Shewanella algae (18) and Staphylococcus aureus (28). These extracts contain different organic compounds such as saponins, terpenes, sterols, and proteins, which could be responsible for their activity. These results suggest that microorganisms are an effective alternative to replace harmful chemical substances currently used in antifouling coatings. The extracts, being less toxic, are potential inhibitors or retardants of the epibiotic colonization process.